Research the Impact of Online Marketing on Customers Perceived Value of Vietnamese Joint Stock Commercial Banks - Hoai, Le Thi; Quyet, Chu Ba (Journal of Ecohumanism, 2024)
Research the impact of online marketing on customer perceived value at Joint Stock Commercial Banks (JSCBs) is a significant and highly applicable topic in marketing and management business. The analysis and conclusions from this study can provide valuable information about how online marketing influences customer perceptions and the value they place on their banking experience. This will help businesses better understand how to interact with customers, optimize their marketing strategies, and improve customer relationships to increase business efficiency. The authors have proposed a theoretical model and scale based on a comprehensive study of published documents. Through qualitative research and in-depth interviews with experts, an official research model and scale have been formed, including six variables (five independent variables and one dependent variable) with 33 observed variables. Conducting quantitative research with a sample size of N = 355, the model has been determined to suggest five independent variables with 28 observed variables and one dependent variable with 5 observed variables (through Cronbach’s Alpha and EFA coefficients), and the model adjusted model with five independent variables with 27 observations and one dependent variable with 05 observed variables. The study has determined the impact of online marketing on customer perceived value at Vietnamese joint stock commercial banks, arranged in descending order of influence: ((1) Online Communication; (2) Online Customer Service; (3) Online Offer; (4) Online retail Pricing, and (5) Online Distribution.